Determinar el potencial energético para la generación de electricidad con el biogás emitido en el relleno sanitario del cantón Salcedo - Villacis Toapanta, Diego Enrique (2016)
In the present study was determined the energy potential for electricity generation with biogas emitted in the sanitary landfill of San Pedro de Jachaguango belonging to Salcedo city was determined, where biogas is generated by the natural decomposition of solid waste and this is absolved freely and dispersed in the air, causing pollution and producing unpleasant odors in the sector, so was identified of the problems ofsanitary landfill that is the lack of treatment of biogas producing pollution of natural resources such as air, land and Water. For which was initiated with this research project, with the determination of the amount of solid waste entering final disposal, after sorting recyclables waste was obtained a value of 6461469 kg of solid waste generated in 2015.